2022
DOI: 10.3389/fncel.2022.1022754
|View full text |Cite
|
Sign up to set email alerts
|

A glial perspective on the extracellular matrix and perineuronal net remodeling in the central nervous system

Abstract: A structural scaffold embedding brain cells and vasculature is known as extracellular matrix (ECM). The physical appearance of ECM in the central nervous system (CNS) ranges from a diffused, homogeneous, amorphous, and nearly omnipresent matrix to highly organized distinct morphologies such as basement membranes and perineuronal nets (PNNs). ECM changes its composition and organization during development, adulthood, aging, and in several CNS pathologies. This spatiotemporal dynamic nature of the ECM and PNNs b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 178 publications
(330 reference statements)
0
58
0
1
Order By: Relevance
“…Not so when the PNNs are disrupted and Glu spills out of the synapses as evident from increased [Glu] in the perisynaptic space. As PNNs are known to be degraded by proteolytic enzymes including MMPs and ADAMTSs [6,36,37], it is easy to envision how brain inflammation in the context of injury or disease will break down PNNs and hence allow spillage of K + and Glu into the perisynaptic space. Increases in K + and Glu are known contributors to epilepsy, and at least in glioma-associated epilepsy, it has been demonstrated that inhibition of PNN proteolysis suppresses seizures [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not so when the PNNs are disrupted and Glu spills out of the synapses as evident from increased [Glu] in the perisynaptic space. As PNNs are known to be degraded by proteolytic enzymes including MMPs and ADAMTSs [6,36,37], it is easy to envision how brain inflammation in the context of injury or disease will break down PNNs and hence allow spillage of K + and Glu into the perisynaptic space. Increases in K + and Glu are known contributors to epilepsy, and at least in glioma-associated epilepsy, it has been demonstrated that inhibition of PNN proteolysis suppresses seizures [22].…”
Section: Discussionmentioning
confidence: 99%
“…4) is defined. AldheGFP signal (5), is binarized using automated OTSU function (6), and pericellular AldheGFP area (7), is extracted by intersecting ( 4) and (6) binary images. Synaptic marker vGlut1 (8), image is processed with an automated peak detection function to detect vGlut1 puncta (8).…”
Section: Volumetric Analysis In Imarismentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in neural plasticity are part of the central sensitization process which derives from neuroimmune and neuroinflammatory processes resulting from peripheral nerve injury. The involvement of microglial and astrocyte activation as a result of these is clearly linked to the reshaping of the ECM and concomitant changes in the intercellular interactions at the synapse, which ultimately affect cell signaling and neurotransmission [ 56 ]. The effects of astrocyte activation on expression levels of proteins in the ECM that are associated with this process is also confirmed by our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we observed increased accessibility at several CSPG loci, including Tnr, Bcan, Vcan, Acan, and Ncan 107 (Figure 5C). CSPGs have been found to negatively regulate OPC proliferation, differentiation and remyelination, as well as induce production of pro-inflammatory cytokines 108,109 . Similar to our findings in snRNAseq data, we found that Ts65Dn OPCs exhibited an increase in accessibility at several endoprotease loci, including Mmp15/19, Adam12, and Adamts5/17 loci (Figure 5C), all of which play a role in modulating neuroimmune activity through the regulation of pro-inflammatory cytokine availability and signaling 73,74 .…”
Section: Trisomy Induces Unique Chromatin Accessibility Patterns In T...mentioning
confidence: 99%